Effect of inorganic salt on partition of high‐polarity parishins in two‐phase solvent systems and separation by high‐speed counter‐current chromatography from Gastrodia elata Blume. Issue 4 (18th January 2019) - Dong, Hongjing; Yao, Xue; Liu, Dahui; Zhou, Tao; Wu, Guozhen; Zheng, Xiuhua; Wang, Xiao
Abstract: Parishins are high‐polarity and major bioactive constituents in Gastrodia elata Blume. In this study, the effect of several inorganic salts on the partition of parishins in two‐phase solvent systems was investigated. Adding ammonium sulfate, which has a higher solubility in water, was found to significantly promote the partition of parishins in the upper organic polar solvents. Based on the results, a two‐phase solvent system composed of butyl alcohol/acetonitrile/near‐saturated ammonium sulfate solution/water (1.5:0.5:1.2:1, v/v/v/v) was used for the purification of parishins by high‐speed counter‐current chromatography. Fractions obtained from high‐speed counter‐current chromatography were subjected to semi‐preparative high‐performance liquid chromatography to remove salt and impurities. As a result, parishin E (6.0 mg), parishin B (7.8 mg), parishin C (3.2 mg), gastrodin (15.3 mg), and parishin A (7.3 mg) were isolated from water extract of Gastrodia elata Blume (400 mg). These results demonstrated that adding inorganic salt that has high solubility in water to the two‐phase solvent system in high‐speed counter‐current chromatography was a suitable approach for the purification of high‐polarity compounds.